System Evaluation of a Knowledge-Based Database Design Tool: An Application of the Thesaurus Approach - Mohd Noah, Shahrul Azman; Williams, Michael (Malaysian Journal of Computer Science, 2017)
The use and exploitation of real-world knowledge by a knowledge-based (KB) database design tool was claimed capable of enhancing its performance in terms of processing efficiency, quality of designs produced and appearance of tool's intelligence. However, as to date, there have been no serious attempts made to evaluate these claims. This paper presents such an evaluation of one approach proposed to facilitate the system storage and exploitation of real-world knowledge; the thesaurus approach.